“THE EFFECT OF DIRECT MAIL, TANGIBLE REWARD, INTERPERSONAL COMMUNICATION AND PREFERENTIAL TREATMENT ON POSITIVE WORD OF MOUTH” (An Empirical Study of Credit Card Holder of Mandiri Bank in Malang City) - Ahmed Zulfikar (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims at examining the effect of Direct Mail, Tangible Reward, Interpersonal Communication and Preferential Treatment on Positive Word of Mouth on credit card holder of Mandiri Bank in Malang City partially. The questionnaire has been distributed to 150 respondents who are Credit Card Holder of Mandiri Bank and lived in Malang City. The sampling technique used is purposive sampling and the research instruments were tested using the Validity Test, Reliability Test, and Classical Assumption Test. This research uses Multiple Regression Analysis to analyze the data. The result of multiple regression analysis indicates that Direct Mail, Tangible Reward, Interpersonal Communication and Preferential Treatment are significantly effect on Positive Word of Mouth. It also known that Tangible Reward is the most powerful and dominant variable among all the independent variables. The results of this research can be applied in a marketing strategy for the company and interested parties to maintain and maximize Direct Mail, Tangible Reward, Interpersonal Communication and Preferential Treatment to obtain a positive effect of Positive Word of Mouth on potential customers that can lead to a purchase decision.Keywords: Direct Mail, Tangible Reward, Interpersonal Communication and Preferential Treatment, Word of Mouth.